Senyawa 5,3'-Dihidroksi-7,4'-Dimetoksiflavon dari Kulit Batang Tanaman Akway (Drimys beccariana Gibs) dan Aktivitas Antimalarianya - Tarso Rudiana; Tati Herlina; Euis Julaeha (Jurnal Kimia Valensi, 2018)
Akway (Drimys beccariana Gibs) is an endemic plant of Papua. Ethnobotany is used as a medicinal plant, one of which is used as a malaria drug. This study aims to isolate, determine the chemical structure and evaluate the antimalarial activity of D. beccariana stem bark. Powder of D. beccariana bark is macerated with methanol and fractionated using n-hexane and ethyl acetate. Ethyl acetate extract was fractionated using gradient liquid chromatography (KCV) (n-hexane: ethyl acetate: methanol). The KCV fraction was separated by repeated gravity column chromatography and preparative thin layer chromatography (TLC-P) to obtain Isolate 1. Isolate 1 was determined by spectroscopic methods including UV-Vis, IR, 1D NMR, and 2D. Isolate 1 is determined by its compound structure which is 5,3'-dihydroxy-7,4'-dimethoxyflavone. 5,3'-dihydroxy-7,4'-dimethoxyflavone compounds evaluated antimalarial activity against Plasmodium falciparum in vitro with antimalarial activity better than artemisinin.